Case Report: A case of severe pulmonary hypertension combined with FBN1 mutation associated geleophysic dysplasia - Chen, Ze-yang; Cao, Yuan; Yang, Jie; He, Xue-hua; Liu, Li-ping; Yuan, Yong-hua (Frontiers in Pediatrics, 2025)
BackgroundFBN1 gene mutation-associated geleophysic dysplasia (GD) leads to the formation of complex and refractory pulmonary hypertension (PH) through a multifactorial combination of precapillary factors, postcapillary factors, and respiratory pathology. However, clinical experience regarding the diagnosis and management of these patients remains limited.Case reportThe patient was admitted to the hospital with severe PH symptom. He exhibited typical facial features, severe disproportionate short stature, and was diagnosed with GD following the identification of a heterozygous mutation in exon 42 of the FBN1 gene via whole-exome sequencing. Pulmonary artery pressure was reduced after admission and treatment with treprostinil, but mitral stenosis progressively worsened. The patient was then treated with mitral valvuloplasty + atrial septal windowing at an outside hospital, the procedure was successful, but the patient could not be weaned from ECMO after the procedure.ConclusionThis case expands our understanding of therapeutic strategies for PH associated with FBN1 mutation–related GD. Treprostinil may be effective in the treatment of these patients. Given the risk of progressive pulmonary disease, early surgical intervention for mitral valve pathology may be crucial for improving prognosis.